Menu costs at work: Restaurant prices and the introduction of the Euro - Bart Hobijn; Federico Ravenna; Andrea Tambalotti (Federal Reserve Bank of New York, 2004)
Restaurant prices in the Euro area saw an unprecedented increase after the introduction of the Euro. We use an extension of commonly used models of sticky prices and argue that the increase in restaurant prices can be explained by menu costs. The extension we use involves the state-dependent decision of firms about when to adopt the Euro. Two main mechanisms drive the result. First, our model concentrates otherwise staggered price increases around the introduction of the Euro. Second, before the adoption of the Euro, prices do not reflect marginal cost increases expected to occur after the changeover. This horizon effect disappears as soon as the new currency is adopted, contributing to a jump in prices at that time. For realistic parameter values, the model generates a blip in inflation of the same magnitude observed in the data
Keywords: E31; E63; L89; 330; Anpassungskosten; Preisrigidität; Monopolistischer Wettbewerb; Inflation; Gastronomie; Euro; EU-Staaten